2015
DOI: 10.1097/mjt.0b013e318274e0a1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intrathecal Esmolol on Heat-Evoked Responses in a Postoperative Pain Model

Abstract: Perioperative tachycardia and hypertension are often treated with esmolol, a short-acting β1-adrenoceptor antagonist. Besides its cardiac effect, esmolol is reported to exert antinociceptive effects. This study examined the efficacy of intrathecal (IT) esmolol on pain responses in a postoperative pain model. Male Sprague-Dawley rats (250-300 g) were anesthetized with sevoflurane and an IT catheter was implanted. Six days after catheter implantation, a postoperative pain model was established by plantar incisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Interestingly, patients received esmolol infusion consumed significantly lower dose of IO and PO fentanyl; a finding suggesting an analgesic effect for esmolol. These findings go in hand with Ono et al [35] who experimentally, found intrathecal administration of esmolol produced antinociceptive effects of short duration in a rat PO pain model. Clinically, Lee et al [36] found pretreatment with esmolol or remifentanil equally decreased pain during propofol injection with no significant differences in pain incidence or severity.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, patients received esmolol infusion consumed significantly lower dose of IO and PO fentanyl; a finding suggesting an analgesic effect for esmolol. These findings go in hand with Ono et al [35] who experimentally, found intrathecal administration of esmolol produced antinociceptive effects of short duration in a rat PO pain model. Clinically, Lee et al [36] found pretreatment with esmolol or remifentanil equally decreased pain during propofol injection with no significant differences in pain incidence or severity.…”
Section: Discussionmentioning
confidence: 57%
“…It has been shown that esmolol, as a selective short-acting antagonist, has analgesic effects in addition to cardiovascular effects. For example, the study by Ono and colleagues showed that intrathecal administration of esmolol had analgesic effects on postoperative pain in animals [ 4 ]. Bhawna and his colleagues showed that esmolol can reduce the need for opioids after abdominal surgery [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A report on in vivo administration of esmolol alone explored the effect of intrathecal administration in a postoperative pain model ( Ono et al, 2015 ). The postoperative pain model was established with the use of a plantar incision.…”
Section: Beta Blockers Affect the Excitation Transmission Of The Nerv...mentioning
confidence: 99%